Role of Dynamic Actin Cytoskeleton Remodeling in Foxp3+ Regulatory T Cell Development and Function: Implications for Osteoclastogenesis - Dohnke, Sebastian; Moehser, Stephanie; Surnov, Alexey; Kurth, Thomas; Jessberger, Rolf; Kretschmer, Karsten; Garbe, Annette I. (Frontiers in Immunology, 2022)
In T cells, processes such as migration and immunological synapse formation are accompanied by the dynamic reorganization of the actin cytoskeleton, which has been suggested to be mediated by regulators of RhoGTPases and by F-actin bundlers. SWAP-70 controls F-actin dynamics in various immune cells, but its role in T cell development and function has remained incompletely understood. CD4+ regulatory T (Treg) cells expressing the transcription factor Foxp3 employ diverse mechanisms to suppress innate and adaptive immunity, which is critical for maintaining immune homeostasis and self-tolerance. Here, we propose Swap-70 as a novel member of the Foxp3-dependent canonical Treg cell signature. We show that Swap-70-/- mice have increased numbers of Foxp3+ Treg cells with an effector/memory-like phenotype that exhibit impaired suppressor function in vitro, but maintain overall immune homeostasis in vivo. Upon formation of an immunological synapse with antigen presenting cells in vitro, cytosolic SWAP-70 protein is selectively recruited to the interface in Treg cells. In this context, Swap-70-/- Treg cells fail to downregulate CD80/CD86 on osteoclast precursor cells by trans-endocytosis and to efficiently suppress osteoclastogenesis and osteoclast function. These data provide first evidence for a crucial role of SWAP-70 in Treg cell biology and further highlight the important non-immune function of Foxp3+ Treg cells bone homeostasis mediated through direct SWAP-70-dependent mechanisms.